Aversive drug cues reduce cigarette craving and increase prefrontal cortex activation during processing of cigarette cues in quitting motivated smokers. (24th August 2021) - Kunas, Stefanie L.; Bermpohl, Felix; Plank, Irene S.; Ströhle, Andreas; Stuke, Heiner
Abstract: Aversive drug cues can be used to support smoking cessation and create awareness of negative health consequences of smoking. Better understanding of the effects of aversive drug cues on craving and the processing of appetitive drug cues in abstinence motivated smokers is important to further improve their use in cessation therapy and smoking‐related public health measures. In this study, 38 quitting motivated smokers underwent functional magnetic resonance imaging (fMRI) scanning while performing a novel extended cue‐reactivity paradigm. Pictures of cigarettes served as appetitive drug cues, which were preceded by either aversive drug cues (e.g., smokers' leg) or other cues (neutral or alternative reward cues). Participants were instructed to rate their craving for cigarettes after presentation of drug cues. When aversive drug cues preceded the presentation of appetitive drug cues, behavioural craving was reduced and activations in prefrontal (dorsolateral prefrontal cortex) and paralimbic (dorsal anterior cingulate cortex [dACC] and anterior insulae) areas were enhanced. A positive association between behavioural craving reduction and neurofunctional activation changes was shown for the right dACC. Our results suggest that aversive drug cues have an impact on the processing of appetitive drug cues, both on a neurofunctional and a behavioural level. A proposed model states that aversive drug‐related cues activate control‐associated brain areas (e.g., dACC), leading to increased inhibitory control on reward‐associated brain areas (e.g., putamen) and a reduction in subjective cravings. Abstract : Three possible pathways through which aversive drug cues impact on appetitive drug cue reactivity in smokers can be distinguished: aversive drug cues (1) reduce craving and decrease reactivity of the mesolimbic reward network, (2) increase activation in control areas and (3) increase prefrontal down‐regulation of mesolimbic areas. We found a reduced craving for cigarettes in smokers on a behavioural level. The pattern of activated brain areas suggests increased cognitive control (of reward), as well as down‐regulation of brain reward areas.